Queens of the summer hotel [compact disc] - Mann, Aimee (Super Ego Records, 2021)
Aimee Mann started working on a musical, based on the memoir Girl, Interrupted. But it takes years for a Broadway show to get produced. So Aimee ended up going into the studio and recording all the songs for the musical herself, and this is the result.